Distribution and abundance of the mangrove bivalves Isognomon ephippium (Linnaeus) and Cyrena ceylonica (Chemnitz) in Andamans - Thangavelu, R.; Soundararajan, R.; Poovannan, P. (Indian Journal of Fisheries, 2011)
Investigations were carried out on the occurrence, distribution, population density, sex ratio, percentage edibility and total biomass of the oyster Isognomon ephippium in three different locations namely Sippighat creek, Mithagari jetty and Diglipur port area and the clam Cyrena ceylonica in the marshy areas around Sippighat and Bimbleton creeks of Andaman islands. The study revealed that the density of oyster population was high in Sippighat than the other two locations and the clam was more abundant in the mangrove creeks and backwater canal of Sippighat.